2017
DOI: 10.18203/2349-2902.isj20174173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tzanakis scoring system in acute appendicitis: a prospective study

Abstract: Background: Tzanakis scoring system is a combination of clinical evaluation, ultrasonography and laboratory marker of inflammatory response, used as accuracy of diagnosis of acute appendicitis. Objective of this study was to evaluate the predictability of Tzanakis scoring system in preoperative diagnosis of acute appendicitis and compare its accuracy with histopathological examination (HPE).Methods: A prospective non-randomized study was designed to study those patients who suspected clinically as acute append… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
3
5
0
Order By: Relevance
“…ROC analysis for prediction of delayed appendectomy has shown that with an AUC value of 0.696 and a sensitivity of 69% and a specificity of 60.8%, this score has sufficient discriminatory ability to distinguish patients with delayed and timely appendectomy. This coincides with data from the literature where this test shows the greatest sensitivity and specificity, even up to 99% sensitivity, 91% specificity, and an average diagnostic accuracy of 95% [27][28][29].…”
Section: Discussionsupporting
confidence: 90%
“…ROC analysis for prediction of delayed appendectomy has shown that with an AUC value of 0.696 and a sensitivity of 69% and a specificity of 60.8%, this score has sufficient discriminatory ability to distinguish patients with delayed and timely appendectomy. This coincides with data from the literature where this test shows the greatest sensitivity and specificity, even up to 99% sensitivity, 91% specificity, and an average diagnostic accuracy of 95% [27][28][29].…”
Section: Discussionsupporting
confidence: 90%
“…This has probably led to a more accurate preoperative diagnosis and hence the lower rate of negative appendectomy in our setup as was also observed by Kumar et al in their study. 8 In our study the sensitivity and specificity of Tzanakis score in diagnosing acute appendicitis was 90.66% and 73.68% respectively. The overall diagnostic accuracy was 86.23% with positive predictive value of 97.89% and negative predictive value of 36.84%.…”
Section: Discussionsupporting
confidence: 45%
“…9 Sigdel et al found the effectiveness of Tzanakis score in 100 patients undergone emergency appendectomy having sensitivity, specificity, and overall diagnostic accuracy was 91.48% and 66.66% and 90%. 10 12 A larger negative appendectomy rate of 15% to 25% has been allowed in the past in the cost of preventing appendicular perforation in the studies of Raja et al and Joshi et al 13,14 Hsiao et al conducted a retrospective study and found sensitivity and specificity for an Alvarado score ≥7 were 60% and 61% respectively. 15 Rezak et al, in their retrospective study, found a higher sensitivity and specificity-92% and 82% respectively.…”
Section: Discussionmentioning
confidence: 99%